(untitled) (Vietnam Journal of Community Medicine, 2023)
The 5S model is the beginning of a quality enhancement initiative to improve safety, efficiency, or other patient-centered aspects. Applying 5S on all types of equipment is to improve the quality of Can Tho University of Medicine and Pharmacy Hospital. It is believed to have some positive effects to the working environment since items are arranged in order, creating more spacious area. Objective: The study aimed to evaluate results of applying 5S on all types of facilities at Can Tho University of Medicine and Pharmacy Hospital after 1-year intervention. Method: The pre-post study design was applied, sampling all 166 equipments in use at Can Tho University of Medicine and Pharmacy Hospital. Results: The results showed that the intervention process achieved positive changes in all 5 types of equipment. After 12 months of intervention, the effectiveness index ranged from 20.24% to 42.65%. Conclution: Thus, the applied 5S intervention methods have shown certain effectiveness in quality improvement in hospital.